Pelatihan Dilan (Distilasi Sederhana) sebagai Upaya Revitalisasi Program Serenisasi di Malang: Dilan (Simple Distillation) Training as an Effort to Revitalize the Serenization Program in Malang - Firdaus, Favian Rafif; Naima, Fathnin Ulya; Akbar, Achmad Naufal Maulana; Haq, Nimas Rizqi Firdausy; Lestari, Dewi; Setiawan, Catur Dian; Widyowati, Retno (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Codo Village, located in Malang Regency, once held a serenization program. Local PKK women pioneered this program, whose actions were realized through a movement to plant lemongrass throughout the vacant village land to avoid the spread of dengue fever in 2016. A lack of knowledge about the potential of lemongrass plants caused a decline in enthusiasm for the serenization program, marked by many broken lemongrass plants. So, the DILAN (Simple Distillation) training provides a solution to revitalize the serenization program, starting with the formation of cadres, delivery of materials related to lemongrass plants and simple extraction of essential oils using the DILAN method, introduction to e-commerce, supervision and evaluation. The result of this program is that PKK women can produce marketable products from essential lemongrass oil, such as soap, aromatherapy candles, and carbolic acid. The products produced are codo asri and can be obtained from online sales sites. This program can increase the knowledge, productivity and abilities of the population to improve the community's economic status so that the revitalization program can be successfully implemented.